Strong inequalities for the iterated Boolean sums of Bernstein operators: Dedicated to Professor Heiner Gonska on the occasion of his 70th anniversary. - CHENG, Li; ZHOU, Xinlong (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
In this paper we investigate the approximation properties for the iterated Boolean sums of Bernstein operators. The approximation behaviour of those operators is presented by the so-called strong inequalities. Moreover, such strong inequalities are valid for any individual continuous function on [0, 1]. The obtained estimate covers global direct, inverse and saturation results. Mathematics Subject Classification (2010): 41A05, 41A25, 41A40.